The con men : a history of financial fraud and the lessons you can learn - Gough, Leo (Financial Times series, 2013)
Financial fraud, whether large or small is a persistent feature of the financial markets. If you scratch the surface of the investment world you'll find a continuous stream of major financial scandals which are almost unbelievable in the sheer scale of their subterfuge. The Con Men shines a spotlight on some of these gargantuan frauds from the last 25 years. It questions how these men did it, why they did it, how there were able to get away with it, proposes strategies and tactics so that the reader can avoid being swindled.